Effects of Three Anti-Seizure Drugs on Cholinergic and Metabolic Activity in Experimental Status Epilepticus - Imran, Imran; Koch, Konrad; Schöfer, Henrik; Lau, Helene; Klein, Jochen (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Purpose. Status epilepticus (SE) is characterized by recurrent seizure activity and can be drug-resistant. Knowledge of neuronal and metabolic activity of the brain during SE may be helpful to improve medical care. We here report the effects of three anti-seizure drugs on changes of acetylcholine energy metabolites and oxidative stress during SE. Methods. We used the lithium-pilocarpine model in rats to induce SE and in vivo-microdialysis to monitor cholinergic and metabolic activity in the hippocampus. We measured extracellular concentrations of acetylcholine, glucose, lactate, pyruvate, glycerol and isoprostanes before and during SE, and after acute treatment with pregabalin, valproic acid, and levetiracteam. Results. Upon onset of SE, acetylcholine (ACh) release increased six- to eightfold. Glucose was increased only transiently by 30% but lactate levels rose four-fold, and extracellular concentrations of glycerol ten-fold. Isoprostanes are markers of oxidative stress and increased more than 20-fold. Two hours after pilocarpine adminstration, rats were treated with pregabalin (100 mg/kg), levetiracetam (200 mg/kg) or valproic acid (400 mg/kg) by i.p. injection. All three drugs stopped seizure activity in a delayed fashion, but at the doses indicated, only animals that received levetiracetam reached consciousness. All drugs reduced ACh release within 60-120 minutes. Lactate/pyruvate ratios, glycerol and isoprostanne levels were also reduced significantly after drug administration. Conclusions. Hippocampal ACh release closely follows seizure activity in SE and is attenuated when SE subsides. Pregabalin, valproic acid and levetiracetam all terminate seizures in the rat SE model and attenuate cholinergic and metabolic changes within two hours.